Flexural performance of concrete filled tubes with high tensile steel and ultra-high strength concrete - Xiong, Ming-Xiang; Xiong, De-Xin; Liew, J.Y. Richard (Journal of constructional steel research, 2017)
The use of high strength materials in steel-concrete composite members is expected to provide greater resistance meanwhile fulfilling the requirements of sustainable construction. Many of the modern design codes place some limits on the strength of steel and concrete in designing steel-concrete composite members due to limited test data and design experience on their applications in construction. The use of high strength materials was found to have noticeable benefits in high-rise building construction. To extend their applications, a comprehensive experimental program has been carried out to investigate the behaviour of concrete filled steel tubes (CFSTs) with high tensile steel and ultra-high strength concrete at ambient temperature. This paper presented new test results on the structural performance of CFST members subject to flexural loads. High tensile steel with yield strength up to 780MPa and ultra-high strength concrete with compressive cylinder strength up to 180MPa were used. The test results seek to clarify if the cross-section plastic moment resistance can be achieved if high tensile steel and ultra-high strength concrete are used in CFST members. The maximum moment resistance from tests were compared with the analytical results predicted by Eurocode 4 method. Then design recommendations were provided so that Eurocode 4 method could be safely extended to determine the flexural resistance of CFST members with high tensile steel and ultra-high strength concrete. •Flexural tests on concrete filled tubes with steel of 780MPa and concrete of 180MPa were introduced.•Plastic moment resistance is achieved but flexural stiffness should be modified.•Recommendations to flexural member design in Eurocode 4 are provided.•Test database of concrete filled tubes subject to flexural loads are established.